Formation of carbohydrate-functionalised polystyrene and glass slides and their analysis by MALDI-TOF MS - Weissenborn, Martin J.; Wehner, Johannes W.; Gray, Christopher J.; Šardzík, Robert; Eyers, Claire E.; Lindhorst, Thisbe K.; Flitsch, Sabine L. (Beilstein Journal of Organic Chemistry, 2012)
Glycans functionalised with hydrophobic trityl groups were synthesised and adsorbed onto polystyrene and glass slides in an array format. The adsorbed glycans could be analysed directly on these minimally conducting surfaces by MALDI-TOF mass spectrometry analysis after aluminium tape was attached to the underside of the slides. Furthermore, the trityl group appeared to act as an internal matrix and no additional matrix was necessary for the MS analysis. Thus, trityl groups can be used as simple hydrophobic, noncovalently linked anchors for ligands on surfaces and at the same time facilitate the in situ mass spectrometric analysis of such ligands.
Keywords: carbohydrate array; conductive tape; MALDI-TOF MS; nonconductive surface; trityl-mediated adhesion